Towards integration of transcranial Doppler in the management of severe TBI in LICs and LMICs: A cohort retrospective study - Nourou Dine A. Bankole; François de Paule D.K. Adjiou; Moussa Denou; Mustapha Hemama; Nizare El Fatemi; Mamoun Faroudy; Moulay Rachid El Maaqili; Abdessamad El Ouahabi (Interdisciplinary Neurosurgery, 2022)
Background: Medical first-line management to fight against raised intracranial pressure due to severe TBI in LICs and LMICs is still precarious, especially with the lack of means for adequate monitoring of intracranial pressure. Objective: In the cohort retrospective study, we aimed to show if the TCD could have an impact on decision-making to operate and on the GOS. Methods: Patients treated at bi-institutional between March 2017 and July 2019, were included if they had Moderate to Severe TBI treated surgically. Variables associated with the outcome were tested using uni and multivariable analyses. Results: One hundred and thirty-six TBI patients were admitted for management during the study period, 21 and 44 were excluded respectively because they were managed medically only, and were benign trauma. Seventy-one(71) patients were included in the final analysis. They had a mean age of 44.27 years old (+/− 15.99) at diagnosis and there was a male predominance (n = 59, 83,1%). 52(73.2%) of them benefited from TCD. The mean time between admission and the surgery in a cohort of patients from TCD monitoring was 6 h ± 4 vs 8 h ± 3 (P = 0.003). The mean GOS in the cohort group with non-TCD was 4,7 ± 1,1 versus 4,3 ± 1,1(P = 0.047)in the non-TCD cohort group. The paired test revealed statically significantly positive in the use of TCD for Severe TBI, Z = -3.859, P = 0.044 with a median effect (r = 0.23). Conclusion: TCD has an impact on the early decision to go for DC and has a median effect on GOS.